Biološka zdravila za zdravljenje multiple skleroze - Bratkovič, Tomaž (Farmacevtski vestnik, 2024)
Multiple sclerosis is an incurable neurodegenerative disease, characterized by demyelination and neurodegeneration, leading to disability. With early detection and immediate continuous treatment with modern disease-modifying drugs (including biological medicines), the relapse rate and intensity can be decreased, and the accumulation of demyelinating plaques in the central nervous system diminished, thereby slowing the disease progression. In this review, we summarize the results of clinical trials evaluating efficacy and safety of biological medicines for the treatment of multiple sclerosis. In particular, monoclonal antibodies (natalizumab, alemtuzumab, ofatumumab, ocrelizumab and ublituximab) display high efficacy, but are associated with certain serious adverse effects, such as cytokine release syndrome, (opportunistic) infections and autoimmune diseases.
Keywords: alemtuzumab; anti-CD20 monoclonal antibodies; Biološka zdravila; glatiramer; interferon beta; monoklonska protitelesa proti CD20; Multipla skleroza; multiple sclerosis; natalizumab